Media Game Online Edukatif dalam Mendukung Kemampuan Literasi Awal Anak Usia Dini: Systematic Literature Review Tahun 2023–2026 - Inayatul farihah; Umi Nadzifah; Aliwan Aliwan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study aims to systematically examine the role of educational online game media in supporting early literacy skills among young children during the 2023–2026 period. The research employed a Systematic Literature Review (SLR) method using the PRISMA 2020 framework. Data sources were obtained from scientific journal articles indexed in Google Scholar, Scopus, DOAJ, and SINTA, with inclusion criteria focusing on studies discussing educational online games and early childhood literacy. The analysis process followed the stages of identification, screening, eligibility, and inclusion, followed by thematic analysis to identify research patterns, trends, and key findings.The findings indicate that the most frequently used educational online game media include mobile learning games, web-based games, and interactive platforms such as Wordwall, Quizizz, and Kahoot. These media have been shown to contribute positively to the development of letter recognition, phonological awareness, vocabulary acquisition, and early reading skills among young children. Furthermore, research trends during the 2023–2026 period reveal an increasing adoption of game-based learning approaches that emphasize not only cognitive development but also children's motivation, engagement, and learning experiences. In conclusion, educational online game media represent an effective learning strategy for supporting early literacy development in early childhood education. The findings suggest that the integration of digital technology in early childhood learning should be supported by teachers’ competencies, appropriate pedagogical planning, and the development of learning media that align with the characteristics and learning needs of young children.